2011
DOI: 10.1080/14748460.2011.616326
|View full text |Cite
|
Sign up to set email alerts
|

The climate of inclusive classrooms: the pupil perspective

Abstract: This paper offers insights into learning experiences in inclusive classrooms, gained by giving voices to pupils about their perceptions of themselves and their opinions on classroom climate. A positive response pattern is identified concerning academic and social dimensions of schools, while the overall picture concerning the dimension of participation is more blurred. The paper argues for further explorations of the concept of educational participation in inclusive settings, not only with a focus upon the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
0
17
0
4
Order By: Relevance
“…Children's perceptions of the classroom climate were assessed using the Climate of Inclusive Classrooms questionnaire (Tetler & Baltzer, ). This instrument can be used to assess the climate in primary educational settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's perceptions of the classroom climate were assessed using the Climate of Inclusive Classrooms questionnaire (Tetler & Baltzer, ). This instrument can be used to assess the climate in primary educational settings.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from individual characteristics, the present authors asked for the children's opinion about their classroom climate. Additionally, children were assessed on their emotional and social integration with school and peers, as well as their motivation to learn.Children's perceptions of the classroom climate were assessed using the Climate of Inclusive Classrooms questionnaire(Tetler & Baltzer, 2011). This instrument can be used to assess the climate inprimary educational settings.…”
mentioning
confidence: 99%
“…Norwich and Kelly (2003) studied children's views on inclusion and concluded that taking account of children's perspectives can inform policy and practice. Tetler and Baltzer (2011) carried out research on the climate of inclusive classrooms seen from the children's perspective. Based on 14 interviews, their research found that involving children in the planning and evaluation of teaching supported their autonomy and engagement.…”
Section: The Field Of Research: Inclusive Education and Pupils' Perspmentioning
confidence: 99%
“…By one hand, students identify the academic but also the social dimensions of schools as important aspects of positive school social climate (Tetler & Baltzer, 2011). By another hand, the importance of the teachers role in identifying and reporting deficits and needs in students socioemotional functioning is been increasingly acknowledged (Lundervold, Posserud, Ullebo, Sorensen, & Gillberg, 2011).…”
Section: Teachers' Perceptions Of Schooling Socio-emotional Needsmentioning
confidence: 99%